Radiological assessment of the structural shielding adequacy of the radiotherapy facility at Korle-Bu Teaching Hospital, Accra, Ghana - Adu, S.; Emi-Reynolds, G.; Schandorf, C.; Darko, E.O.; Gyekye, P.K. (Radiation Protection Dosimetry, 2012)
A 60Co radiotherapy source with an initial activity of 185 TBq has exhausted its useful half-life and has been replaced with a 222 TBq 60Co source at the Korle-Bu Teaching Hospital; a radiological assessment was performed to ascertain the shielding integrity of the facility. Dose rate at selected critical positions were calculated for the old and new sources. Dose rate measurements were also performed at these critical locations for the new source. The dose rates at all the critical locations of the public and staff access areas were within the recommended dose rate limit of 0.5 and 7.5 μSv h -1 for the public and controlled area, respectively. The concrete biological shielding at the facility at the moment is adequate enough to attenuate the gamma photons from the new 222 TBq 60Co source. High dose rates were recorded at the entrance to the treatment room, it is therefore recommended that optimisation of procedures should be encouraged to restrict activities in this area. © The Author 2011. Published by Oxford University Press. All rights reserved.
Keywords: Radiological assessment; structural shielding adequacy; radiotherapy; Korle-Bu Teaching Hospital